Characteristics sources, and formation of organic aerosols in the central Rocky Mountains - Schurman, Misha Iris, author; Collett, Jeffrey L., advisor; Kreidenweis, Sonia M., committee member; Henry, Charles S., committee member; Fischer, Emily V., committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: aqueous; biomass burning; cloud; organic aerosol; particle transport; photochemistry